Potensi Pemanfaatan Perangkat Diagnostik ELISA serta Variannya untuk Deteksi Patogen Tanaman - Yadi Suryadi; Ifa Manzila; muhammad Machmud (Balai Besar Penelitian dan Pengembangan Bioteknologi dan Sumber Daya Genetik Pertanian, 2009)
Diseases aremajor constrains to agricultural crop productions in Indonesia.In the current free world trade system, the chances ofintroduction of plant quarantine agents are higher, and aredifficult to control, due to importation of seeds and otherplanting materials. Principles of the plant disease controlinclude exclusion and eradication. Early and accurate diseasediagnosis is an early and important step for a successfuldisease control. Enzyme-linked Immunosorbent Assay(ELISA) is a promising technique for an aneffective andefficient disease diagnosis. Some advantages of techniqueover the conventional and molecular diagnostic techniquesare economical use of reagents, high sensitivity, relativelysimple and quick, suitable for large numbers of samples,and adaptable for automation. In the past decade, severalvariants and kits of ELISA had been introduced, such asIndirect ELISA, F(ab’)2 ELISA, Dot Blot ELISA, and ImmunoFluorescence Assay (ELFA). Based on the solid membraneused, the Dot Blot ELISA some variants were developed,such as the NCM-ELISA, Tissue Blotting ELISA, dan Paper ELISA. The ELISA variants had different limit of detection levels. The limit detection of the variants for bacteria is ranging from 102-105 cells/ml, while those for viruses were from 1-10 ng/ml. The times required for the ELISA tests ranging from 5-48 hours. Models and components of ELISA kits for some viral and bacterial plant pathogens had been developed, but more are still needed since generally for each pathogen needs a different kit. The commercially available ELISA kits are limited in numbers, some of themare for pathogens that are not present in Indonesia. Production of ELISA kits for domestic uses will be more effective and efficent, particularly for pathogens that are present in the country. The ELISA kits are applicable not only fo detection and identification of pathogens, but also forecological study of the pathogens in conjuction with epidemiological study of the disease. This paper is a brief review on the ELISA technique and its variants and potential uses for detection of plant pathogens